2002
DOI: 10.1080/0968759022000039073
|View full text |Cite
|
Sign up to set email alerts
|

Employers' Perceptions and Practice in the Employability of Disabled People: A survey of companies in south east UK

Abstract: This article reports a foundation survey of the extent of employment of disabled people in three sectors of industry-transportation, IT and nancial services-in two UK counties, identi es which speci c disabilities and limitations on personal skills are seen by employers as the greatest impediments to employment, proposes a new model for analysis by using a modi cation of established recording models and provides a springboard for further work. The survey reported here was based on structured interviews with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
(4 reference statements)
0
17
0
1
Order By: Relevance
“…Clearly such factors make the decision to disclose a precarious option. Although many studies have identified discriminatory practices from co‐workers (Stevens 2002, McLaughlin et al. 2004), in this study disclosure to colleagues often resulted in consistently useful support and acceptance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Clearly such factors make the decision to disclose a precarious option. Although many studies have identified discriminatory practices from co‐workers (Stevens 2002, McLaughlin et al. 2004), in this study disclosure to colleagues often resulted in consistently useful support and acceptance.…”
Section: Discussionmentioning
confidence: 67%
“…2002). However, despite the Disability Discrimination Act (HMSO 1995), support for disabled people in employment is generally considered to be inconsistent (Stevens 2002). Within the UK National Health Service (NHS), Europe's largest employer, the recruitment and retention of disabled health care staff have been an issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Várias pesquisas que analisam as dificuldades das pessoas com deficiência para se inserirem no mercado de trabalho têm concluído que existe falta acentuada de conhecimento em relação à capacidade de trabalho dessas pessoas e desconhecimento do que seja a deficiência (Anache, 1996;Carreira, 1997;Lancillotti, 2001;Mantoan, 1997;Oliveira, 1993). Também as pesquisas internacionais identificam a discriminação das pessoas com deficiência como dificuldades para o processo de inserção (Batavia & Schriner, 2001;Henderson & Bryan, 2004;Kamal, 2004;Popovich, Scherbaum, Scherbaum, & Polinko, 2003;Stevens, 2002;Woodhams & Danieli, 2000, dentre outros).…”
Section: I I Introdução Ntrodução Ntrodução Ntroduçãounclassified
“…Other studies reported employer positive attitudes towards possible career advancement of people with disabilities (Kregel & Unger, 1993). In a study based in the United Kingdom, Stevens (2002) found that employers expressed positive attitudes about applicants with disabilities, although very few respondents had actually hired members of this group. Participants, however, did indicate interest in accepting applications from prospective employees.…”
Section: Positive Attitudes Toward Hiring and Accommodationsmentioning
confidence: 99%